Kasus Pemerolehan Bahasa Jepang - Ilvan Roza (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2009)
The child is given the ability to learn language at birth, starting from the words spoken by their parents or from others around him. Stage by stage the development of child language acquisition increases, beginning from mimicking and repeating the words and the sounds he heard. In addition, children’s language development is also influenced by circumstances of social life. In addition, it is also influenced by a variety of local languages in stages according to the place where parents and the child live Kata Kunci: pemerolehan, bahasa, psikolinguistik